Let z = sin(x).
.. z^2 -2z = 2
.. z^2 -2z +1 = 3
.. (z -1)² = 3
.. z -1 = ±√3
.. z = 1 -√3 . . . . . the positive solution is extraneous
sin(x) = 1 -√3
1/4 and you choose three different toppings for a sundae
<span>Simplifying
4x + 20 = 6x + -10
Reorder the terms:
20 + 4x = 6x + -10
Reorder the terms:
20 + 4x = -10 + 6x
Solving
20 + 4x = -10 + 6x
Move all terms containing x to the left, all other terms to the right.
Add '-6x' to each side of the equation.
20 + 4x + -6x = -10 + 6x + -6x
Combine like terms: 4x + -6x = -2x
20 + -2x = -10 + 6x + -6x
Combine like terms: 6x + -6x = 0
20 + -2x = -10 + 0
20 + -2x = -10
Add '-20' to each side of the equation.
20 + -20 + -2x = -10 + -20
Combine like terms: 20 + -20 = 0
0 + -2x = -10 + -20
-2x = -10 + -20
Combine like terms: -10 + -20 = -30
-2x = -30
Divide each side by '-2'.
x = 15
Simplifying
x = 15</span>
Answer:
Hope you find the help you need on this sorry , i couldnt find the answer :( good luck !!
Step-by-step explanation:
Answer
-2
Step-by-step explanation:
learn how to do your work f^gg0+